Viabilidade de Bifidobacterium longum 5¹A e Bl05 em bebidas lácteas fermentadas com diferentes culturas iniciadoras - Luciana Rodrigues Faleiro (2015)
The main studies of trends in the development of new food products show sensory aspects, convenience and practicality, health and wellness as the main features of interest to consumers. Among the products that appear to meet this latest trend, functional foods stand out, especially probiotics. Bifidobacterias are used as probiotics worldwide in various foods. However, factors such as interactions with lactic acid bacteria, fermentation conditions and product pH affect the viability of these microorganisms. The brazilian law requires the minimum amount of 108 UFC of viable probiotic cells in the daily recommendation of the product at the time of consumption. The objectives of the present study were to determine the culture medium for selective enumeration of strains of Bifidobacterium longum 51A and BL05 in the presence of different starter cultures and evaluate viabiltiy of bifidobacteria during fermentation and refrigerated storage of fermented dairy beverages processed differently. Culture media allowing high recovery rate of B. longum cells when compared to the reference medium, agar MRS, and that would inhibit starter culture bacteria were tested. Fermented dairy beverages produced were added lyophilized or frozen Bifidobacterium culture and fermented with different compositions of starter cultures (co-culture of Lactobacillus delbrueckii subsp bulgaricus (Lb 340) + Streptococcus thermophilus (St-TA40); S. thermophilus St-TA40; S. thermophilus St1) and with addition of bifidobacteria in two stages of processing, at the beginning and in the end of fermentation. The proteolytic activity of S. thermophilus strains was also analysed. St1 strain showed, lower proteolytic activity, lower acidification ability, which resulted in a longer fermentation and a lower rate of post acidification of fermented dairy beverages compared to the St-TA40 culture. The medium Bile-MRS was suitable for enumeration of B. longum strains in the presence of the starter cultures used. The use of the frozen culture activated in MRS broth compared to the use of the lyophilized culture provided higher cell viability of B. longum BL05 during refrigerated storage. Fermentation time was greatly reduced when both B. longum strains were added at the beginning of fermentation of the fermented beverages with St1. However, the moment of addition of both strains of B. longum did not alter the fermentation time and the survival of the bifidobacteria in fermented dairy beverages with the co-culture St- TA40+Lb340. The B. longum 51A strain was less resistant to stress conditions, showing a reduction in the count of viable cells of 2 to 3 logarithm in comparison with B. longum BL05 strain after 28 days of storage, in the group of bifidobacteria added beverages at the beginning and in the end of fermentation, respectively.